2016
DOI: 10.3390/rs8121032
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Coupling between Vegetation Leaf Area and Climate in a Multifunctional Watershed, Northwestern China

Abstract: Accurate detection and quantification of vegetation dynamics and drivers of observed climatic and anthropogenic change in space and time is fundamental for our understanding of the atmosphere-biosphere interactions at local and global scales. This case study examined the coupled spatial patterns of vegetation dynamics and climatic variabilities during the past three decades in the Upper Heihe River Basin (UHRB), a complex multiple use watershed in arid northwestern China. We apply empirical orthogonal function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 78 publications
1
8
0
Order By: Relevance
“…A study of arid and semi-arid regions in China demonstrated that precipitation significantly positively affected GPP, NPP, and LAI, while the temperature was negatively correlated with NPP, and had no correlation with GPP [21]. Hao et al [22] found that increases in temperature and precipitation in north-west China during the past three decades had a positive impact on annual mean LAI. In most parts of China, the temperature is the main climatic factor affecting the change of NPP.…”
Section: Introductionmentioning
confidence: 99%
“…A study of arid and semi-arid regions in China demonstrated that precipitation significantly positively affected GPP, NPP, and LAI, while the temperature was negatively correlated with NPP, and had no correlation with GPP [21]. Hao et al [22] found that increases in temperature and precipitation in north-west China during the past three decades had a positive impact on annual mean LAI. In most parts of China, the temperature is the main climatic factor affecting the change of NPP.…”
Section: Introductionmentioning
confidence: 99%
“…However, within-country migration to Ulaanbaatar is accompanied by the depopulation of rural areas, while in IM a strong influx of population from other Chinese provinces has compensated the rural (and, in particular, nomadic) population decline. These variations in socioecological parameters are compounded by spatiotemporal variation in climate (Liu et al 2013, as well as interactive feedbacks among the elements of SES (Hardin 1968, Chen et al 2015b, Hao et al 2016a, Allington et al 2017, Hessl et al 2018.…”
Section: Social-ecological Systems (Ses) On the Mongolian Plateaumentioning
confidence: 99%
“…These two RCP scenarios are more representative and widely used for future climate forcing. The RCP4.5 scenario explores the long-term climate system response to the stabilizing the anthropogenic components of radiative forcing [33], while the RCP8.5 scenario represents the highest greenhouse gas emissions [34]. We chose these two typical climate change scenarios to focus the effect of climate change on evapotranspiration in the future based on normal and high emissions, respectively, including the effects of low and middle emissions of RCP 2.6 and RCP 6.0 on evapotranspiration.…”
Section: Data Setsmentioning
confidence: 99%
“…Since variables in terrestrial ecosystems are characterized by non-linearity and high dimensionality, the Empirical Orthogonal Function (EOF) analysis and Singular Value Decomposition (SVD) analysis techniques are widely used to represent the variation in dominant spatiotemporal patterns; the relative importance of each pattern is in explaining observed variation across space [33][34][35]. First, according to the spatial mode, EOF was conducted to analyze temporally varying spatial patterns of annual evapotranspiration, and corresponding time coefficients that describe the magnitude of the variation of the spatial mode.…”
Section: The Statistical Analysismentioning
confidence: 99%